Ovarian activity and vaginal resistance in postpartum anestrus Sahiwal cows - SAHU, S K; TIWARI, R P; MISHRA, U K; MUKHERJEE, K (The Indian Journal of Animal Reproduction, 2023)
Postpartum anestrus Sahiwal cows (n=4) which had not shown the signs of estrus three months after parturitionand did not show presence of corpus lutcum in one of the ovary at two examinations made by rectal palpation 11 days apartwere selected for present investigation. Ovaries of all the experimental animals were monitored at 4 days interval for 24days by the use of Real time B-mode ultrasonography (Scanner 200 EMC/ Pie MediG&l)- WFc-the development of .-arianfollicle with 5 Mhz transducer. On each examination the diameter of the largest follicle in each ovary was measured. Vaginalmucus impedance was measured daily for 24 days with the help of vaginal probe and impedance meter. The mean folliculardiameter at days 0, 4, 8,12,16,20 and 24 were 3.9:t0.60, 6.72:tl.60, 5.57:tl.89, 6.72:tl.75, 8.6:!:0.67, 7.97:t0.65 and10.23:t0.87 mm respectively. Changes in VMI indicated a clear increasing and decreasing pattern at a very short intervalwith very high individual variation. Correlation ( r ) between VMI and follicular diameter was negative and significant (r =-0.83 P < 0.01). It was concluded by the present investigation that ovarian activity in prolonged postpartum ancstrus cowhas negative correlation of VMI with follicular diameter. VMI could be a cost and time effective means to determine theovarian functional status in true ancstrus postpartum animals, which arc beyond the reach of· rectal palpation.
Keywords: VMI; ovarian activity; postpartum anestrus; cattle